Language of concern on the academic performance of Malaysian children in foster care / Cherish How - Cherish , How (2019)

(untitled)
In Malaysia, school teachers and foster caregivers attend to the needs of children in foster home. As the children reach the age of eighteen, they have to leave foster care system and take charge of their own needs. In most cases, due to the lack of academic credential, securing a job and getting a place to live are some of the challenges they encounter. As such, teachers and caregivers play an important role in foster children’s lives to ensure the educational needs of these children are addressed. It is essential to explore the degree of concern that teachers, caregivers, and foster children have towards academic achievements. This study examines the realisation patterns of speech act of concern from teachers’, foster caregivers’ and foster children’s responses in relation to the poor academic performance of children in foster care. Based on the language use, it also evaluates their stages of concern and investigates the types of academic needs and issues of children in foster care. Searle’s (1976) Speech Act Categories and Hall and Hord’s (1987) Stages of Concern are employed as frameworks for analysis. Content analysis is used to qualitatively analyse the narratives elicited from the semi-structured interviews of teachers, caregivers and foster children from selected secondary school and foster homes in Klang Valley, Malaysia. Various categories of speech act and stages of concern are coded and identified. Findings reveal that concern is voiced through the categories of speech acts and representative act is highly utilised by teachers and caregivers to describe, explain, and complain about problems in managing foster children; while intention to help foster children excel in school is highly prominent at the stage of refocusing. The findings also illustrate the frequent use of expressive act amongst foster children to express concern on their low level of comprehension in the iv subjects they could not excel. Both teachers and caregivers are concern about the need for improving foster children’s poor academic performance and lack of attention. The older foster children are more concern about their weak subjects than the younger ones. This study allows Social Welfare Agency to recognise the constraints and issues teachers and caregivers are hampered with in order to provide support to improve the educational services for foster children. Moreover, foster children too could reach out for assistance in the achievements of their academic needs. With helping to improve foster children’s academic performance, they would have better careers in the future.